SISTEM REKOMENDASI PERTANIAN PADA ARSITEKTUR AGRIBUSINESS E-MARKETPLACE (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2020)
Currently the development of information technology has driven the development of e-commerce which is quite promising in Indonesia. This development has brought an era of new digital-based creative developments. Agriculture as one of the economic and community welfare bases in Indonesia needs to be developed and supported with digital finance. Several agricultural markets have been established in Indonesia to help farmers to participate in digital economic activities. Some e-commerce systems that have been built in Indonesia only help the downstream process or the marketing process. While farmers need information that can help them for agricultural purposes. Machine learning technology uses data collected in the agricultural marketplace system to be used in building a social assessment system. Recommendations for agricultural activities are adjusted to the cost of agriculture, location of agriculture, pricing of agricultural commodities at the time of receipt and timing of agricultural activities. In this research an analysis and design of an agricultural e-commerce system will be provided to provide farmers to sell their agricultural products at competitive prices and help farmers to obtain information that can be used to plan further agricultural activities.
Keywords: E-Commerce; Agriculture; Recommendation System; Requirement Analyst